Conceptual Change Inquiry Curriculum and Traditional Lecture Approach: Preservice Teacher’s Perceptions of Learning - Lloyd Mataka; Rex Taibu (Journal of Education in Science, Environment and Health)
A quasi-experimental treatment control group design was used to investigate the effect of a conceptual change curriculum, Multi-Step Inquiry approach, on students’ perception of their learning in a science classroom. This started with the development of a workbook that explicitly focused on conceptual understanding, followed by the development and validation of an inventory to explore students’ perceptions of learning. Interpretation of data involved the use of inferential and descriptive statistics. The inferential statistics included t-tests, ANOVA, Pearson correlations, and regressions. Cohen’s d effect sizes facilitated further interpretation of the data. The analysis shows potential for the Multi-Step Inquiry to improve students’ perceptions. These results provided room for recommendations for both research and teaching.